2020
DOI: 10.1093/mnras/staa1671
|View full text |Cite
|
Sign up to set email alerts
|

The advection-dominated accretion flow for the anticorrelation between the X-ray photon index and the X-ray luminosity in neutron star low-mass X-ray binaries

Abstract: ABSTRACT Observationally, an anticorrelation between the X-ray photon index Γ (obtained by fitting the X-ray spectrum between 0.5 and 10 keV with a single power law) and the X-ray luminosity L0.5-10 keV, i.e. a softening of the X-ray spectrum with decreasing L0.5-10 keV, is found in neutron star low-mass X-ray binaries (NS-LMXBs) in the range of $L_{\rm 0.5\!-\!10\,keV}\sim 10^{34}\!-\!10^{36}\ \rm erg\ s^{-1}$. In this paper, we explain the observed anticorrelat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 56 publications
0
9
0
3
Order By: Relevance
“…Combining the explanations for the anticorrelation between the X-ray photon index Γ and L 0.5−10keV with the X-ray spectra analyzed with the single power-law model, and the positive correlation between η and L 0.5−10keV with the two-component model for a fraction of the sources in the sample, we conclude that in the range of L 0.5−10keV ∼ 10 34 − 10 35 erg s −1 , the softening of the X-ray spectra is due to the increase of the thermal soft X-ray component, while in the range of L 0.5−10keV ∼ 10 35 − 10 36 erg s −1 , the softening of the X-ray spectra is probably due to the evolution of the power-law component itself. As a summary, in the study above for explaining the anticorrelation between Γ and L 0.5−10keV , it has been shown that the value of f th can be constrained to be less than 0.1, and is very probably to be much smaller values, i.e., ∼ 0.003 − 0.005 (Qiao & Liu 2020b).…”
Section: A Summary On Qiao and Liu 2020abmentioning
confidence: 87%
See 4 more Smart Citations
“…Combining the explanations for the anticorrelation between the X-ray photon index Γ and L 0.5−10keV with the X-ray spectra analyzed with the single power-law model, and the positive correlation between η and L 0.5−10keV with the two-component model for a fraction of the sources in the sample, we conclude that in the range of L 0.5−10keV ∼ 10 34 − 10 35 erg s −1 , the softening of the X-ray spectra is due to the increase of the thermal soft X-ray component, while in the range of L 0.5−10keV ∼ 10 35 − 10 36 erg s −1 , the softening of the X-ray spectra is probably due to the evolution of the power-law component itself. As a summary, in the study above for explaining the anticorrelation between Γ and L 0.5−10keV , it has been shown that the value of f th can be constrained to be less than 0.1, and is very probably to be much smaller values, i.e., ∼ 0.003 − 0.005 (Qiao & Liu 2020b).…”
Section: A Summary On Qiao and Liu 2020abmentioning
confidence: 87%
“…Further, in Qiao & Liu (2020b), based on the sample of nonpulsating NS-LMXBs in Wijnands et al (2015), and adding some more non-pulsating NS-LMXBs from Parikh et al (2017) and Beri et al (2019), we explain the anticorrelation between the Xray photon index Γ (obtained by fitting the X-ray spectra between 0.5 and 10 keV with a single power law) and L 0.5−10keV , i.e., the softening of the X-ray spectra with decreasing L 0.5−10keV , in the range of L 0.5−10keV ∼ 10 34 − 10 36 erg s −1 by adjusting the value of f th . Moreover, it is shown that a fraction of the sources in Qiao & Liu (2020b) are once reported to be fitted with the twocomponent model (with XMM − Newton X-ray data), i.e., a thermal soft X-ray component plus a power-law component.…”
Section: A Summary On Qiao and Liu 2020abmentioning
confidence: 95%
See 3 more Smart Citations